Diagnostic Accuracy of Fine Needle Aspiration Cytology in Diagnosis of Tuberculous Lymphadenitis (Journal of Enam Medical College, 2019)
Background: Tuberculosis is still a global health problem. Most common presentation of extrapulmonary tuberculosis is tuberculous lymphadenitis. In our setting, keeping huge burden of tuberculosis in mind, clinicians have to depend on pathological diagnosis of enlarged lymph nodes, i.e., cytomorphology with acid-fast staining in diagnosing these cases so that diagnosis and management of such cases can be initiated quickly. Fine needle aspiration cytology (FNAC) of lymph nodes has been a simple, rapid and cost-effective procedure for diagnosis of various causes of lymphadenopathies.Objective: To determine the diagnostic accuracy of fine needle aspiration cytology in providing a diagnosis of tuberculous lymphadenitis patients in Bangladesh.Materials and Methods: This cross-sectional study was done on 317 subjects in Bangabandhu Sheikh Mujib Medical University (BSMMU) in collaboration with icddr,b. After clinical examination, fine needle aspiration (FNA) was done. The FNA materials were processed for Papanicoulaou staining (PAP stain), Ziehl-Neelsen staining and culture for the diagnosis of tuberculosis. Sensitivity, specificity, positive and negative predictive values of FNAC were determined where culture was taken as the gold standard.Results: Initially 351 clinically suspected tuberculous lymphadenitis patients were enrolled, but 34 cases were excluded due to diagnosis of malignancy. Among them 123 were male and 194 were female. Mean age was 27.91±13.16 years. Among the subjects 95.9% presented with cervical lymphadenopathy, others presented with lymphadenopathy of axillary or other groups of lymph nodes. The results of cytomorphological diagnosis of TB were in 58.36% cases, and culture was positive in 23.3% cases. Sensitivity, specificity, positive predictive value and negative predictive value of cytomorphological diagnosis were 79.7%, 48.1%, 31.9% and 88.6% respectively.Conclusions: FNAC is an effective diagnostic method for tuberculous lymphadenitis. It can diagnose granulomatous inflammation as well as reactive and other disease conditions including malignancies, thereby providing more information about the patient’s disease status.J Enam Med Col 2019; 9(1): 30-33